Pengaruh Cash Holding, Investment Opportunity Set, dan Dividend Policy terhadap Firm Value - Dewi, Atika Somantri; Nurbaiti, Beti; Ningrum, Endah Prawesti; Nuryati, Tutty; Yulaeli, Tri (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The consumer non-cyclicals sector has experienced sluggish stock price movements in recent years due to weakened currency performance and declining purchasing power. These conditions raise concerns about the factors influencing firm value in this sector. This study aims to examine the effect of cash holding, investment opportunity set, and dividend policy on firm value in non-cyclical consumer goods companies listed on the Indonesia Stock Exchange. The research applies a quantitative approach using secondary data from annual financial reports for the 2020–2023 period, involving 46 companies selected through purposive sampling. Data analysis was conducted using panel data regression with the common effect model, supported by classical assumption tests and hypothesis testing. The results show that, partially, investment opportunity set has a significant positive effect on firm value, while cash holding and dividend policy do not significantly influence firm value. Simultaneously, all three variables jointly affect firm value. These findings highlight the importance of future investment prospects as a key driver of firm value, whereas cash reserves and dividend distributions appear to play a less decisive role in investor decision-making.